Cotside EEG monitoring using computerised spectral analysis. - Aziz, S S (1986)
The application and interpretation of computerised spectral analysis of the neonatal electroencephalogram (EEG) using the Neuroscience Berg Fourier Analyser (BFA) is described. Recordings are immediately available at the cotside. Electrophysiological changes can be recognised by individuals with no previous experience in EEG technology. The compact nature of the analysis allows long periods of recording to be viewed within minutes. In addition to the unequivocal demonstration of both clinical and subclinical seizures, the BFA is useful in the evaluation of interseizure activity--that is, disturbance of sleep patterns, electrical output, and hemisphere asymmetry.